2020
DOI: 10.1016/j.jvs.2019.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Two-year evaluation of fenestrated and parallel branch endografts for the treatment of juxtarenal, suprarenal, and thoracoabdominal aneurysms at a single institution

Abstract: Objective: Despite numerous recent pivotal and small-scale trials, real-world endovascular management of juxtarenal aneurysms (JRA), suprarenal aneurysms (SRA), and thoracoabdominal aortic aneurysms (TAAA) remains challenging without consensus best practices. This study evaluated the mortality, graft patency, renal function, complication, and reintervention rates for fenestrated and parallel endografts in complex aortic aneurysms repairs.Methods: This retrospective review of consecutive included patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“… 19 Use of EndoAnchors (Medtronic), endovascular stiches with helical screws, is also suggested to decrease gutter leak. 20 Bannazadeh and colleagues 21 also reported that oversizing should be adjusted by number of chimney grafts. They recommend use of 20% oversizing for the main graft when <2 chimney grafts are used and 30% oversizing for 3 chimney grafts.…”
Section: Endovascular Taaa Repair With Chimney/parallel Graftsmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 Use of EndoAnchors (Medtronic), endovascular stiches with helical screws, is also suggested to decrease gutter leak. 20 Bannazadeh and colleagues 21 also reported that oversizing should be adjusted by number of chimney grafts. They recommend use of 20% oversizing for the main graft when <2 chimney grafts are used and 30% oversizing for 3 chimney grafts.…”
Section: Endovascular Taaa Repair With Chimney/parallel Graftsmentioning
confidence: 99%
“…They recommend use of 20% oversizing for the main graft when <2 chimney grafts are used and 30% oversizing for 3 chimney grafts. 21 However, they did not comment on the size of main graft with 4 chimney grafts, which would often be required for TAAA repair. As such, most of the literature regarding chimney grafts is for juxtarenal and pararenal abdominal aortic aneurysm—and there are scarce data available for extensive TAAA.…”
Section: Endovascular Taaa Repair With Chimney/parallel Graftsmentioning
confidence: 99%
See 2 more Smart Citations
“…A lack of precise and objective information regarding aneurysm neck anatomy, pooling of shortneck aneurysms with aneurysms without a neck as well as aneurysms of the visceral aortic segment and thoracoabdominal aortic aneurysms seriously limits the value of most published evidence. [11][12][13][14] These sources of bias, confounding and heterogeneity, have been consistently recognised as weaknesses in the evidence base by authors of systematic reviews. 15 16 There is therefore a pressing need to generate comparative effectiveness evidence in this area with adequate internal and external validity.…”
Section: Introductionmentioning
confidence: 99%